Cobb–Douglas Analysis of Technical Efficiency in Banyuwangi Batik Small and Medium Enterprises - Mochamad Ardi Setyawan; Mokhamad Eldon (Synergy in Economic & Business Management, 2025)
This study examines the technical efficiency and production elasticity of batik small and medium enterprises (SMEs) in Banyuwangi Regency, Indonesia. Using panel data from 12 active SMEs observed between 2018 and 2023, the Cobb–Douglas production function is estimated through panel regression techniques. Model selection tests indicate that the Random Effect Model is the most appropriate specification. The results reveal that capital and production equipment significantly and positively affect output, whereas labor exhibits a significant negative elasticity, suggesting overutilization and managerial inefficiency. Raw materials show no statistically significant contribution to production performance. The estimated return to scale equals 1.63, indicating increasing returns to scale and implying that proportional input expansion generates more than proportional output growth. The model explains 89% of output variation, demonstrating strong explanatory power. These findings highlight the importance of capital access, technology upgrading, and labor optimization in improving SME productivity. The study provides empirical evidence to support efficiency-oriented policy interventions for traditional creative industries.